2011
DOI: 10.1128/jvi.00640-11
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the History of Maize Streak Virus Strain A Dispersal To Reveal Diversification Hot Spots and Its Origin in Southern Africa

Abstract: Maize streak virus strain A (MSV-A), the causal agent of maize streak disease, is today one of the most serious biotic threats to African food security. Determining where MSV-A originated and how it spread transcontinentally could yield valuable insights into its historical emergence as a crop pathogen. Similarly, determining where the major extant MSV-A lineages arose could identify geographical hot spots of MSV evolution. Here, we use model-based phylogeographic analyses of 353 fully sequenced MSV-A isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…Monocotinfecting mastreviruses have previously been found throughout Africa (including the South-west Indian Ocean islands: SWIO), Europe, Japan, Southeast Asia, the island of Vanuatu, and Australia. Mastreviruses previously found on SWIO islands such as La Réunion and Mauritius include various maize streak virus (MSV) strains, sugarcane streak Réunion virus (SSRV) and sugarcane streak virus (SSV) [13,19,25,26].…”
mentioning
confidence: 99%
“…Monocotinfecting mastreviruses have previously been found throughout Africa (including the South-west Indian Ocean islands: SWIO), Europe, Japan, Southeast Asia, the island of Vanuatu, and Australia. Mastreviruses previously found on SWIO islands such as La Réunion and Mauritius include various maize streak virus (MSV) strains, sugarcane streak Réunion virus (SSRV) and sugarcane streak virus (SSV) [13,19,25,26].…”
mentioning
confidence: 99%
“…Possibly, the strain of MSV-A infecting maize at the transition zone was more virulent than that of the forest and coastal savannah, hence the more severe symptoms at the transition zone than the forest and the coastal savannah zones. It has also been reported [1,32] that virulent MSV isolates cause earlier symptoms with wider and more chlorotic streaks than the mild isolates. This could explain why higher levels of incidence and severity of MSD were recorded at the transition zone than the forest and the coastal savannah zones.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to differences in environmental conditions and varying virulence of MSV strains occurring at various agroecological zones. Important differences in the virulence of different MSV-A subtypes in maize have been reported [32]. Subtypes A1, A2 and A5 isolates produce the severest symptoms, subtypes A3 and A6 isolates produce intermediate symptoms, while subtype A4 isolate produce the mildest symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven strains of MSV are known (Varsani et al 2008), but only the strain MSV-A causes major yield losses in maize. Sequence analyses revealed that MSV-A probably originated in southern Africa in the 1860s by recombination and spread on average 32.5 km per year (Monjane et al 2011).…”
Section: Introductionmentioning
confidence: 99%